CO-INCIDENTAL FINDING OF SUPRATENTORIAL EPENDYMOMA IN PATIENT WITH GRAVES’ DISEASE - Fezal, Nurshafinaz Salmah Mohd; Hussain, Suhaimi (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION Ependymomas are rare primary tumours of the cranial nervous system in children, which can be classified into supratentorial, infratentorial and spinal cord. They may present with neurological deficits or an increase in intracranial pressure symptoms based on their anatomical sites. Their symptoms may overlap with Graves’ disease. It is postulated that the occurrence of Graves’ disease might be due to alterations in the immunological response involving the hypothalamus-pituitary-thyroid axis that results in the formation of TSH antibodies. CASE A 10-year-old male who was previously well presented with lethargy, loss of appetite, recurrent vomiting and loss of weight for the past month. Clinically, he had bilateral exophthalmos, no ophthalmoplegia or lid lag, and a pulse rate of 120 beats/min. His thyroid function test showed overt hyperthyroidism (TSH 0.60 m IU/L, T4 24.70 pmol/L). However, his thyrotropin receptor antibodies are still pending. Thyroid ultrasound was consistent with thyroiditis. He was started on thyroid storm treatment and his condition improved. He presented again with reduced consciousness with a Glasgow coma scale of 10/15, unequal pupil and hyperreflexia of the left limbs. Urgent brain CT brain revealed a right cerebrum intra-axial tumour. He underwent tumour excision. Histopathology revealed a supratentorial ependymoma. Post-operative Cranial MRI showed tumour size reduction measuring from 7.9 x 6.4 x 9.1 cm to a residual of 2.7 x 2.5 x 2.7 cm over the right parietal lobe. Carbimazole was continued and his clinical course was monitored. CONCLUSION This is a rare case of a co-incidental finding of supratentorial ependymoma with Graves’ disease.